Creation Without Creativity - Ella Dawn McGeough; Brendan Flanagan (Technophany)
Written from the perspective of visual artists grappling with the histories and futurities of technology, the authors explore the intricate relationship between creativity, Generative AI, and human-machine collaboration. Through text and images, the authors examine the blurred lines of authorship in AI-generated art, posing questions about identity and authority. To consider Gen AI's role in human-AI collaboration, references span historical perspectives from Plato to the avant-garde and the more recent development of AI “spawn” as digital companions. Highlighting the challenges of aesthetics in the absence of embodied experience, ethical and metaphysical queries arising from AI-driven developments are emphasized, as is the impact of AI on creativity and our understanding of the world and self.